The Relationship Between Dengue Hemorrhagic Fever and Climate Change in Wajo District 2015-2019 - Nurfadhillah Nurfadhillah; Andi Susilawaty; Muhammad Rusmin; Abdul Majid HR. Lagu; Syahrul Basri (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2021)
Dengue Hemorrhagic Fever (DHF) is an acute febrile disease caused by the dengue virus which enters human circulation through the bite of the aedes aegypti mosquito. Significant climate change that occurs over a certain period of time. In other words, climate change is also defined as changes in temperature, rainfall, wind speed and so on. This study aims to determine the relationship between the incidence of dengue hemorrhagic fever and climate change in Wajo Regency. This type of research is an analytical study with a correlation design in which to see the relationship between one variable and another. The results of this study indicate that there is a significant relationship between air temperature, rainfall, humidity and the incidence of dengue bleeding (p = 0.001 and r = -0.403), (p value = 0.001 and r = 0.403), (p value = 0.002 and r = 0.533) and there was no significant relationship between wind speed and the incidence of dengue hemorrhagic fever (p value = 0.632 and r = 0.057). It is hoped that in future studies using different designs, data sources, locations and variables and using all other climate variables that are thought to have a relationship with the incidence of dengue hemorrhagic fever. And secondary data used is longer. Keywords : Dengue Haemorrhagic Fever occurrence, air temperature, rainfall, humidity, wind speed